Analisis Perencanaan Agregat dengan Metode Heuristik - Esa Rahmadona; Gesit Thabrani (Universitas Negeri Padang, 2019)
Purpose-The objectives of this study were to calculate the forecast demand and to develop aggregate production planning for PT XYZ to meet demand with the lowest cost.Methodology–The data were gathered through literature review and secondary data gathered directly from the company itself. The demand data from past three years was used to forecast demand using decomposition, seasonal variation, and multiple regression method. Furthermore, all data were analyzed and used to design aggregate planning by using three strategies namely Chase, Level, and Mixed strategy.Finding–The result of this study shows that the seasonal variation method is the best method to use for forcast the demand on 2019, and chase strategyis the optimal strategy for aggregate production planning. Keywords: heuristic method, production planning, aggregate planning, forecasting